Advantages of Garlic in Treating Hypertension: A Review Article - Liqaa Jameel Ibraheem; Noor Al- Huda Ali A. H. Saeed (Genius Journals, 2023)
Supplements with garlic have shown promise for the control of uncontrolled hypertension by lowering systolic blood pressure (BP) by about (10) mmHg as well as (8) mmHg diastolic, comparable to typical BP medication. Here, we outline scientifically tenable explanations for garlic's ability to reduce blood pressure. Garlic-derived polysulfides increase direct modulation of endothelial nitric-oxide (NO) as well as the vascular gasotransmitter sulfides (H2S), which results in smooth muscle cell relaxation; vasodilation; and a decrease in blood pressure. The effectiveness of a H2S and no signaling pathways is influenced by a few dietary and genetic factors, and this may help to cause hypertension. Organosulfur compounds made from garlic may help treat sulfur deficiency, which may contribute to the etiology of hypertension.
Keywords: Hypertension; Garlic; blood pressure; polysulfides